Retraction Note: LncRNA CTBP1-AS2 sponges miR-216a to upregulate PTEN and suppress endometrial cancer cell invasion and migration - Qing-; Yongxiu Yang; Xiaolei Liang (BMC, 2020)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s13048-020-00754-0.